Study of Glucose-6-phosphate Dehydrogenase (G6PD) Status in Preeclampsia - Faruky, Kazi Salma Binte; Begum, Noorzahan; Begum, Shelina; Ali, Taskina; Ferdousi, Sultana; Amin, Ahsanul Haq (Bangabandhu Sheikh Mujib Medical University Journal, 2010)
Background: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is one of the common enzymopathy and may be one of the risk factor for complicated pregnancy. Objectives: To measure erythrocyte G6PD level in pregnant women with preeclampsia in order to observe this enzyme status and also to measure Hb, TC of RBC, serum bilirubin, reticulocyte count to observe hemolytic status. In addition, to correlate this enzyme level with all these hematological parameters in order to find out any relationships among them. Methods: This cross sectional study was carried out in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbag, Dhaka from January to December 2008. For this, 30 pregnant women with preeclampsia, age ranged from 20 to 34 years during their third trimester (>24th weeks) were studied (group B). They were selected from the Obstetric and Gynae Out Patient Department (OPD) of BSMMU and Bangladesh Medical College Hospital (BMCH) of Dhaka City. For comparison age matched 30 apparently normal pregnant women of the same gestational age (control group - group A) were also studied. They were selected by personal contact. Erythrocyte G6PD level was measured by Spectrophotometric method using kit of Randox. Serum bilirubin, hemoglobin concentration, total count of RBC and reticulocyte count were measured by standard laboratory techniques. For statistical analysis ANOVA, independent sample t test, Chi-square test and Pearson's correlation coefficient test were performed by using SPSS for windows version-12 as applicable. Results: In this study, erythrocyte G6PD level was significantly lower in preeclampsia in comparison to that of control but their percentages of involvement was not statistically significant. In addition, hemoglobin concentration and RBC count were significantly lower and serum bilirubin and reticulicyte count were significantly higher in the study group than those of control group. On the other hand, erythrocyte G6PD level was positively correlated with hemoglobin concentration and total count of RBC while negatively correlated with serum bilirubin and reticulocyte count and all these relationships were statistically significant in the study group. Conclusion: Therefore, this study revealed that presence of G6PD deficiency associated with hemolysis in preeclampsia may act as a contributory factor for the development of this complicated pregnancy. Key words: G6PD; preeclampsia DOI: 10.3329/bsmmuj.v2i2.4758 BSMMU J 2009; 2(2): 56-60